The Kennedy Administration and the Battle over Foreign Aid: The Untold Story of the Clay Committee. Issue 1 (2nd January 2016) - David, Andrew; Holm, Michael
ABSTRACT: President John Kennedy made foreign aid a key component of his Cold War strategy, introducing it with much fanfare in 1961. He increased funding for aid projects and created several agencies aimed at modernising the under-developed world. A year later, aid was under pressure from elements in Congress that doubted both its value and accomplishments. In late 1962, Kennedy commissioned General Lucius Clay to assemble a committee to review the aims and management of America's foreign aid programme. Reflecting the president's desire to ensure optimal value and neutralise opponents, it also indicated Administration belief that the rhetoric of modernisation had overshadowed the relationship between aid and national security. Never intending Clay to assemble a mere rubber stamp Committee, Kennedy specifically tasked the members with investigating aid's role in supporting the "Free World." The effort failed. Scholars traditionally assume that it did so because Clay opposed Kennedy's programme; however, he was supportive of the president's efforts. Instead, its demise came at the hands of an unusual Congressional coalition that enthusiastically cut the president's budget.